1967
DOI: 10.1079/pns19670034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changes in feeding patterns on the performance of pigs

Abstract: A short account of work carried out by the authors was given. A full presentation will be published (Strong, Shirling & Passmore, 1967). The summary of this paper is as follows:Food which provided from 2960 to 7880 kcal in excess of requirements was eaten by sixteen subjects, each for a period of 4 days.The proportion of the nutrients lost in the faeces was not increased during overfeeding.The metabolic rates were in no case increased by an amount equivalent to more than 15% of the excess calories. The increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 104 publications
1
15
0
1
Order By: Relevance
“…There is a plethora of data to indicate that liquid feeding of pigs may significantly reduce production costs, improve growth rates, time to slaughter, lower feed to gain ratio or a combinations of these performance parameters besides offering welfare benefits (Braude 1967 and1971;Jensen and Mikkelsen, 1998;Lawlor et al, 2002;Canibe and Jensen, 2003;Scott et al, 2007). However, there has been little new work on liquid feeding in growing-finishing modern porcine genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a plethora of data to indicate that liquid feeding of pigs may significantly reduce production costs, improve growth rates, time to slaughter, lower feed to gain ratio or a combinations of these performance parameters besides offering welfare benefits (Braude 1967 and1971;Jensen and Mikkelsen, 1998;Lawlor et al, 2002;Canibe and Jensen, 2003;Scott et al, 2007). However, there has been little new work on liquid feeding in growing-finishing modern porcine genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid feeding of pigs can significantly reduce production costs as it allows the use of low, dry matter by-products and can, to some extent, offer welfare benefits under hot, summer conditions (Scott et al, 2007). The advantages of liquid compared with dry feeding include improved growth rates, shorter time to slaughter, improved feed to gain ratio or a combinations of these performance parameters (Braude, 1967 and1971;Jensen and Mikkelsen, 1998;Lawlor et al, 2002;Canibe and Jensen, 2003). For example, average daily live-weight gain (ADG) of newly weaned pigs offered NFLF was 12 6 9.4% higher than those observed following dry feeding (Jensen and Mikkelsen, 1998), and ADG was further increased by offering FLF (Dung et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, a review by Braude (1967) suggested that pigs were often unable to select a diet that adequately met their requirements, and therefore the method could not be considered superior to singlefeeding. And recently, Gourley et al (1993), Owen et aE.…”
Section: The Need Of Application Of Phase Feedingmentioning
confidence: 99%
“…An increase of 4-6% in gain to feed ratio (G:F) has been reported when pigs are fed pellet diets vs. meal diets via conventional dry feeders (Wondra et al 1995b). Besides the advantages of less separation, easier handling, less dust, and better hygienic quality (Flatlandsmo and Slagsvold 1971), pellet feed seems to improve growth and feed efficiency (Braude 1967;Vanschoubroeck et al 1971;Hanke et al 1972;Baird 1973;Braude and Rowell 1966). However, pellet feed does have disadvantages.…”
Section: Introductionmentioning
confidence: 99%